The potent neuroepithelium-promoting activity of Otx2 during gastrulation, as demonstrated by its exogenous epiblast-wide expression in chicken embryos - Takami, Naoya; Kato, Kagayaki; Yoshihi, Koya; Kawamura, Akihito; Iida, Hideaki; Kondoh, Hisato (Frontiers in Cell and Developmental Biology, 2025)
Although Otx2 has been a topic of research for over 3 decades, the role of Otx2 expressed in the brain-forming anterior epiblast during gastrulation has not been clarified. We focused on epiblast regions where Otx2 expression is absent or downregulated, namely, the posterior epiblast and tissue belts along the bending of the neural plate. The developmental events that occurred after filling these gaps with exogenous Otx2 provided information about the roles of Otx2 during gastrulation. The following pleiotropic effects were observed: (1) development of an open and flat midbrain and hindbrain, which occurred by unzippering the previously closed neural tube; (2) precocious neural tube development at the cervical level, which resulted in thick and unclosed neural tissue; (3) absence of the sinus rhomboidalis, where neuromesodermal progenitor (NMP) stem cells multiply to provide a cell source for the trunk posterior extension; and (4) inhibition of somite development. To elucidate the principles underlying these developmental abnormalities, the cellular events were analyzed using live imaging of epiblast cells, the cell states were characterized via transcriptome analysis, and the spatial organization of transcription factor expression was determined by immunohistology. Common Otx2 activities that accounted for these pleiotropic effects were identified: (1) significant promotion of neuroepithelium development, which overrides the bipotential nature of NMPs, resulting in the loss of paraxial mesoderm precursors and multiplying NMP stem cell populations, and (2) the development of bending-refractory neural tissues. Owing to these Otx2 functions, Otx2-expressing anterior epiblast cells develop into vast amounts of brain tissue in advance of trunk neurogenesis, which occurs on a much smaller scale. We did not observe that exogenous Otx2 expression affected CNS regional specification during gastrulation.